2019
DOI: 10.22460/pej.v3i1.1231
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Strategy in Development Prosocial Behavior of Students in Elementary School

Abstract: Entering the digital age all information cannot be selectively displayed. Freedom in the digital age can affect the behavior patterns of students whether positive behavior or negative behavior. In an effort to prevent the emergence of negative behavior in students, it requires an environment that shapes good behavior such as prosocial behavior. Prosocial behavior really needs to be developed to prevent moral degradation. The formation of prosocial behavior can be done in a student environment such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The give of induction and reinforcement with sharing, helping, and cooperation could improve prosocial behavior in children (Ramaswamy & Bergin, 2009). Others stated that prosocial behavior in children could improve through religious-based intervention with giving motivation and modeling strategy (Kuswendi, 2019). On the other hand, Yulianto et al (2019) show that cooperative learning and independence are effective ways to increase prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The give of induction and reinforcement with sharing, helping, and cooperation could improve prosocial behavior in children (Ramaswamy & Bergin, 2009). Others stated that prosocial behavior in children could improve through religious-based intervention with giving motivation and modeling strategy (Kuswendi, 2019). On the other hand, Yulianto et al (2019) show that cooperative learning and independence are effective ways to increase prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, in student-teacher relationships, scholars have shown that the following can promote prosocial behavior: teachers’ expectation and evaluation ( Eisenberg et al, 2006 ), and the attachment and support between teachers and students ( Chang et al, 2004 ). The close relationship between teachers and students plays an important role in internalizing pro social values ( Kuswendi, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways for individuals to create good relationships with others, namely through prosocial behavior or help. Prosocial behavior is a feeling of caring as evidenced by providing assistance or cooperation to benefit other individuals [4]. Prosocial behavior is a positive activity that is beneficial to others, and this action is motivated by oneself without expecting any reward [5].…”
Section: Introductionmentioning
confidence: 99%